Altersolanol B, a fungal tetrahydroanthraquinone, inhibits the proliferation of estrogen receptor-expressing (ER+) human breast adenocarcinoma by modulating PI3K/AKT, p38/ERK MAPK and associated signaling pathways. (25th May 2022) - Siraj, Md Afjalus; Jacobs, Aaron T.; Tan, Ghee T.
Abstract: The present study focused on the apoptosis-inducing effects and cellular signal-modulating properties of altersolanol B (AB), a minor fungal tetrahydroanthraquinone (THAQ) metabolite, in the estrogen receptor positive (ER+) human breast adenocarcinoma cell line, MCF-7. AB demonstrated approximately 4-fold greater antiproliferative activity in ER+ MCF-7 cells (IC50 5.5 μM) compared to the ER-negative (triple-negative) MDA-MB-231 (IC50 21.3 μM). The viability of normal breast fibrocystic epithelial cells, MCF-10A, was unaffected. AB induced intrinsic apoptosis in MCF-7 cells; it triggered the activation of caspase 9 and poly (ADP-ribose) polymerase (PARP), upregulated the expression of pro-apoptotic Bax, and downregulated the expression of anti-apoptotic Bcl-2. AB induced cell cycle arrest at G0/G1, as indicated by the downregulation of key checkpoint proteins operating at the G0/G1 phase of the cell cycle (cyclin D1, CDK4 and CDK2). The observed increase in p21Waf1/Cip1 and p53 expression may facilitate cell cycle arrest, and the subsequent induction of apoptosis. AB lacked significant effects on intracellular ROS levels, while it down-regulated nuclear factor erythroid 2-related factor 2 (Nrf2), and the Nrf2-dependent antioxidant enzyme, heme oxygenase-1. The compound disrupted AKT signaling through the downregulation of phospho-AKT and phospho-FOXO1, and the upregulation of PTEN, a phosphatase and tumor suppressor that negatively regulates the PI3K/AKT pathway. AB also disrupted the phosphorylation of AKT-controlled eukaryotic translation initiation factor, 4E-BP1, and GSK-3β, both of which are aberrantly regulated in human cancer. The AB-dependent downregulation of NF-κB was corroborated by the inhibition of TNFα-induced NF-κB activity as monitored in a luciferase reporter. The NF-κB inhibitory activity of AB was 3-fold more potent than that of the standard inhibitor, N - p -Tosyl-l -phenylalanine chloromethyl ketone. In addition to reducing the pro-survival effects of NF-кB, the inhibition of AKT phosphorylation by AB may also lead to FOXO1-mediated growth arrest and apoptosis. AB upregulated the expression of phospho-MKK4 and phospho-p38, and downregulated the expression of phospho-MEK1/2 and phospho-ERK1/2 indicating opposing effects on the two important oncogenic signaling cascades that are aberrantly activated in many cancers. AB disrupted both the AKT and ERK1/2 signaling pathways leading to apoptosis in ER+ MCF-7 cells through mitochondria-associated mechanisms coupled with the potent inhibition of NF-кB activation. The clinical limitations of multi-agent combination therapy that targets multiple pathways in cancer may potentially be circumvented by using a single molecule, such as AB, that inhibits both AKT and ERK1/2 signaling. Our preliminary study suggested that the THAQ pharmacophore, with its disrupted conjugated ring system and relative redox inactivity, may possess greater mechanistic advantage against ER+ breast cancer when compared to the fully conjugated ring systems of the anthraquinone that possess intrinsic redox activity and DNA interacting ability. This study supports the continued investigation of THAQs as lead molecules in anticancer drug discovery and development. Highlights: Altersolanol B (AB) is a tetrahydroanthraquinone (THAQ) from endophytic Stemphylium solani of Morinda citrifolia. AB is more cytotoxic towards estrogen receptor-positive (ER+) than triple negative breast cancer. Redox inactivity of AB provides mechanistic advantage over anthraquinones. AB induced intrinsic apoptosis and disrupted key cellular signaling pathways. Limitations of combination therapy may be circumvented by a dual pathway inhibitor (AB).